Effects of dehydration during cycling on skeletal muscle metabolism in females - Logan-Sprenger, H. M.; Heigenhauser, G. J.; Killian, K. J.; Spriet, L. L. (Medicine & Science in Sports & Exercise, 2012)
INTRODUCTION: This study investigated the effects of progressive dehydration on the time course of changes to whole body substrate oxidation and skeletal muscle metabolism during 120 min of cycling in hydrated females. METHODS: Subjects (n = 9) cycled for 120 min at approximately 65% VO2peak on two occasions: with no fluid (DEH) and with fluid (HYD) replacement to match sweat losses. Venous blood samples were taken at rest and every 20 min and muscle biopsies taken at 0, 60, and 120 min of exercise. RESULTS: DEH subjects lost 0.9% body mass from 0 to 60 min and 1.1% from 60 to 120 min (2.0% total). HR and core temperature (Tc) were significantly greater from 30 to 120 min, plasma volume (Pvol) loss from 40 to 120 min, and RPE from 60 to 120 min in the DEH trial. There were no differences in VO2 or sweat loss between trials. RER (HYD, 0.85 ± 0.01, vs. DEH, 0.87 ± 0.01) and total CHO oxidation (175 ± 17 vs. 191 ± 17 g) were higher in the DEH trial. Blood (La) was significantly higher in the DEH trial, with no change in plasma free fatty acid and epinephrine concentrations. Muscle glycogenolysis was 31% greater in the DEH trial (252 ± 49 vs. 330 ± 33 mmol/kg dry muscle), and muscle (La) was also higher at 60 min. CONCLUSION: Progressive dehydration significantly increased HR, Tc, RPE, Pvol loss, whole body CHO oxidation, and muscle glycogenolysis, and these changes were already apparent in the first hour of exercise when body mass losses were </= 1%. The increased muscle glycogenolysis with DEH appeared to be due to increased core and muscle temperature, secondary to less efficient movement of heat from the core to the periphery.